2020
DOI: 10.3390/cells9102267
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Fifteen Years of Genome-Wide Association Studies in Age-Related Macular Degeneration

Abstract: Over the last 15 years, genome-wide association studies (GWAS) have greatly advanced our understanding of the genetic landscape of complex phenotypes. Nevertheless, causal interpretations of GWAS data are challenging but crucial to understand underlying mechanisms and pathologies. In this review, we explore to what extend the research community follows up on GWAS data. We have traced the scientific activities responding to the two largest GWAS conducted on age-related macular degeneration (AMD) so far. Altoget… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Almost all patients with advanced AMD are over the age of 60 [2]. Genetic factors are also important, and polymorphisms in over 30 genes have been reported to be associated with increased risk of AMD [3]. Others risk factors such as smoking, uncontrolled hypertension, body mass index above 25 have been reported in previous studies [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all patients with advanced AMD are over the age of 60 [2]. Genetic factors are also important, and polymorphisms in over 30 genes have been reported to be associated with increased risk of AMD [3]. Others risk factors such as smoking, uncontrolled hypertension, body mass index above 25 have been reported in previous studies [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, its predictive effect is manifested through integrating its LD connections with the strong SNPs. Moreover, SNP rs7907130 was mapped to a previously identified gene BTBD16 ( Strunz et al, 2020a ) together with the other strong SNPs. It could potentially be a new AMD susceptibility locus.…”
Section: Resultsmentioning
confidence: 99%
“…We started with a list of 41 genes based on a list identified as genes with top priority and statistical significance combined in a genome-wide association study (GWAS) published by the International AMD Genomics Consortium (IAMDGC). Currently, this is both the most recent and largest AMD GWAS study and reported 52 independent genetic signals distributed over 34 loci associated with AMD at genome-wide significance [ 38 , 61 ]. There was a significantly different expression profile between LC3b −/− and WT (χ2 = 12.02; two-tailed p value = 0.0005) with 8 DEGs out of 37 mouse orthologs identified (depicted in the heat map, Figure 8 ), including Rdh5 , Slc16a8 , and Htra1 .…”
Section: Resultsmentioning
confidence: 99%